Intraocular calcidiol: Uncovering a role for vitamin D in the eye. Issue 197 (March 2020) - Rullo, Jacob; Pennimpede, Tracie; Mehraban Far, Parsa; Strube, Yi Ning; Irrcher, Isabella; Urton, Todd; Bona, Mark; Gonder, Tom; Campbell, Robert J.; ten Hove, Martin; Sharma, Sanjay; Farmer, James; et al.
Highlights: 25-Hydroxyvitamin D3 is minimally present in the aqueous humour of patients with cataract only disease. Patients with various retinal diseases contain quantifiable 25-hydroxyvitamin D3 in the aqueous and vitreous humour. The highest concentration of 25-hydroxyvitamin D3 is found in patients with active neovascularization. 1, 25-Dihydroxyvitamin D3 -generating ( CYP27B1 ) hydroxylases are present in the ciliary body and retina and correlate with VEGF-A expression. Abstract: Vitamin D has emerged as a potentially important molecule in ophthalmology. To date, all ophthalmic data pertaining to vitamin D has been restricted primarily to tear and serum analysis in human patients. Considering the isolated nature of the eye, we sought to determine the presence of intraocular vitamin D in ocular disease. Methods: 25-Hydroxyvitamin D3 (25(OH)D3 ) concentrations were measured in the eye and blood of 120 participants undergoing ophthalmic procedures. Ocular localization of the 1, 25-dihydroxyvitamin D3 -generating (CYP27B1) and deactivating (CYP24A1) hydroxylases was performed by immunohistochemistry. Gene expression of CYP27B1, CYP24A1 and VEGF-A was measured in eyes from patients with and without disease. Results: 25(OH)D3 was quantified in 112 ocular samples. In 40 cataract patient samples, the average 25(OH)D3 concentration was 0.057 ng/mL, compared to 72 retinal disease patient samples, average of 0.502 ng/mL (p < 0.001). Intraocular 25(OH)D3 did not correlate with serum levels of 25(OH)D3 . There was no difference between the level of 25(OH)D3 measured in the aqueous and vitreous humour. The vitamin D-specific CYPs 27B1 and 24A1, strongly localized to complementary regions of the ciliary body, retinal pigment epithelium and neural retina. Gene expression analysis confirmed retinal CYP27B1 correlated strongly with VEGF-A in eyes from diabetic patients (r = 0.92, p < 0.001). Conclusions: Our data confirms that vitamin D is present in the humours of the human eye and that local synthesis/degradation is possible via the ocular CYP27B1 and CYP24A1. This argues for a functional role for local vitamin D production and signaling in the eye and suggests that vitamin D may be an important intraocular mediator in disease pathogenesis.